Model Bone of Komarova Implementation for the sensitivity study of the process of remodelling bony before changes in local factors (2009)
In this article, the implementation of the bone level remodeling model proposed by Komarova is carried out, using a functional block diagram as a tool. The objective of this implementation is to make a sensitivity analysis with respect to the variation of the model parameters and determine the influence of paracrine and autocrine factors on the formation of osteoclasts and osteoblasts. The model was implemented in the Matlab R2007b Simulink commercial package. It was found that each parameter has a well-defined operating range and that, outside it, stability is lost and bone gains or losses are established that can be attributed to systemic bone abnormalities. This work constitutes an advance on the topic of bone remodeling thanks to the fact that, unlike previous works, the variations of the parameters of the remodeling process that lead to possible alterations of the processes of bone metabolism are included, which constitutes a point Starting for the study of diseases and alterations of bone density, and allows the modeling of new bone-related diseases, such as bone metastasis. This study, then, is an advance with respect to the works presented by Komarova and Lemaire and can explain phenomena of metastasis and metabolic alterations such as those described in Manolagas.